Paradigma Maqāsid Syariah Menjadi Disiplin Ilmu - Abidin, Mukhlis (Sharia Faculty Islamic Economic Law Study Department, 2019)
The focus of this paper is on the issue of maqasid sharia from the historical aspect and the paradigm shift in thinking from scientific disciplines that still belong to Ushul Fiqh to become independent disciplines. Maqasid sharia is an attempt to harmonize commands and prohibitions to produce a moderate attitude in capturing messages from religious texts born 14 centuries ago. Maqasid sharia was established as a new independent scientific discipline after the appearance of as-Syatibi, which was later developed by scientists after a change of approach (which was previously only a fiqh approach in the modern approach to maqasid science with multiple disciplines including medical, social and any other sciences which support to take legal conclusion). Maqasid sharia is wisdom from what Allah revealed about law to be made a universal value.